Trasplante pulmonar - Ruiz C., Mauricio (Revista Hospital Clínico Universidad de Chile, 2007)
The lung transplant is a choice for advanced pulmonary disease witch life’s expectation is under two years. Single or bilateral lung transplantation indications depend of underlying lung disease and donors availability. Currently the immunosuppressant therapy has three kinds of drugs including calcineurin inhibitors, purines synthesis inhibitors and corticosteroids. Early complications of lung transplantation are mainly reperfusion injury, anastomosis dehiscence and infections. Acute transplant rejection is a complication during the first year, the diagnosis requires bronchoscopy with bronchoalveolar lavage and trasnbronchial biopsy that helps toexclude pulmonary infections. Bronchiolitis obliterans is a late complication. 1-year and 5-year survival are 78% and 48% respectively.